Investigating the potential of plastic pyrolysis oil-diesel blends in diesel engine: Performance, emissions, thermodynamics and sustainability analysis - Haseeb Yaqoob; Hafiz Muhammad Ali; Uzair Sajjad; Khalid Hamid (Results in Engineering)
The abrupt rise in demand for conventional fuels has become a major cause for concern despite their increasing depletion. That's why the pyrolysis process to make plastic pyrolysis oil (PPO), can be used to prepare fuel as an alternative fuel. The batch pyrolysis reactor was fabricated to produce plastic pyrolysis oil (PPO) from locally sourced grocery bags made of high-density polyethylene (HDPE). The purpose of this study was to thoroughly analyze the performance and emission characteristics of an engine running on up to 15 % PPO-diesel blended fuel. Then, the experimental data obtained from a single-cylinder, four-stroke engine with five distinct speeds ranging from 1000 to 3500 rpm were utilized to undertake energy, exergy, and sustainability assessments. The results showed that DPO5 had a maximum brake power of 1.92 kW at 2500 rpm. At 3500 rpm, the engine achieved a thermal efficiency of 47.44 % for diesel and 51.6 % for DPO5 blended fuel. Furthermore, DPO15 produced the least quantity of CO2 at all engine speeds. DPO5 has the highest sustainability index, 1.52 at 2500 rpm. As a result, our research found that a low-level PPO-diesel fuel blend may be effectively injected into diesel engines without requiring any modifications.